Design, synthesis and evaluation of reversible and irreversible monoacylglycerol lipase positron emission tomography (PET) tracers using a ‘tail switching’ strategy on a piperazinyl azetidine skeleton - Chen, Zhen (J Med Chem, 2019)
Monoacylglycerol lipase (MAGL) is a serine hydrolase that degrades 2-arachidonoylglycerol (2-AG) in the endocannabinoid system (eCB). Selective inhibition of MAGL has emerged as a potential therapeutic approach for the treatment of diverse pathological conditions including chronic pain, inflammation, cancer and neurodegeneration. Herein we disclose a novel array of reversible and irreversible MAGL inhibitors by means of tail switching on a piperazinyl azetidine scaffold. We developed a lead irreversible-binding MAGL inhibitor 8, and reversible-binding compounds 17 and 37 which are amenable for radiolabeling with (11)C or (18)F. [(11)C]8 ([(11)C]MAGL-2–11) exhibited high brain uptake and excellent binding specificity in the brain towards MAGL. Reversible radioligands [(11)C]17 ([(11)C]PAD) and [(18)F]37 ([(18)F]MAGL-4–11) also demonstrated excellent in vivo binding specificity towards MAGL in peripheral organs. This work may pave the way for the development of MAGL-targeted positron emission tomography (PET) tracers with tunability in reversible and irreversible binding mechanism.